Materials and applications for sensors and transducers III proceedings of the 3rd International Conference : selected, peer reviewed papers from the 3rd International Conference on Materials and Applications for Sensors and Transducers, (IC-MAST 2013), September 13-17, 2013, Prague, Czech Republic - Vlachos, D. S.; Hristoforou, E. (Key engineering materials, 2013)
ICMAST-2013 is an international interdisciplinary conference covering research and development in the field of material science, especially those materials used for sensors, actuators, and all kind of devices used for transducing physical signals. Furthermore, ICMAST-2013 aims to bring together scientists, engineers and product designers in order to fulfill the gap between research and development. The topics of this proceedings books include: New materials development, Fabrication technology, Sensing principles and mechanisms, Actuators, Optical devices, Electrochemical devices, Mass-sensitive